2019
DOI: 10.15809/irriga.2019v24n2p289-302
|View full text |Cite
|
Sign up to set email alerts
|

Produção Sazonal De Duas Espécies Forrageiras Irrigadas

Abstract: Produção sazonal de duas espécies FORRAGEIRAS irrigadAS     Jhésmila Ingridy Bueno1; Giuliani do Prado1; Adriano Catossi Tinos1; Rafael Rech Bruscagin1 e Gessyka Roberti Volpato1   1Departamento de Engenharia Agrícola - DEA, Universidade Estadual de Maringá - UEM, Rodovia PR 482, km 45, CEP: 87.820-000, Cidade Gaúcha-PR, Brasil. E-mail: jhesmilabueno@hotmail.com, gprado@uem.br, actinos@uem.br, rafaelrechbruscagin@hotmail.com, gessyka_volpato@hotmail.com.     1 RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This fact indicated that ET o showed a relationship with the availability of solar radiation, as expected. A similar pattern was observed by Bueno et al (2019), when evaluating the effect of irrigation on two grass species during the period from May/2018 to June/2019. The authors found that ET o was influenced by incident solar radiation and air temperature.…”
Section: Climatic Conditions and Crop Coefficient (K C )supporting
confidence: 82%
See 1 more Smart Citation
“…This fact indicated that ET o showed a relationship with the availability of solar radiation, as expected. A similar pattern was observed by Bueno et al (2019), when evaluating the effect of irrigation on two grass species during the period from May/2018 to June/2019. The authors found that ET o was influenced by incident solar radiation and air temperature.…”
Section: Climatic Conditions and Crop Coefficient (K C )supporting
confidence: 82%
“…Thus, the higher MSEs% values are probably the result of the use of a constant K c , considering that it is intrinsically related to the ratio between the total area of the canopy and the occupied area of the soil, defined as the leaf area index (LAI) and the height of the crop. Bueno et al (2019) found that after eight cuts of two pasture species, the largest dry and fresh matter yield occurred in the period from November to January, corresponding to summer, which indicates that seasonality influences the forage.…”
Section: Performance Of the Thornthwaite And Mather Modelmentioning
confidence: 92%
“…Algumas pesquisas vêm sendo realizadas comparando o desempenho destas forrageiras tropicais com e sem irrigação. Na maioria dos casos a produtividade sob irrigação têm sido superior (ANTONIEL et al, 2016;BUENO et al, 2019;DANTAS et al, 2016;GOMES et al 2015;2017;OLIVEIRA et al, 2016;SANCHES et al, 2016;2017). Mas também existem casos onde a irrigação não teve efeito sobre a produtividade (DUPAS et al, 2016;LOPES et al, 2016).…”
Section: Nos Processos De Intensificação Da Pecuária O Pasto As Culti...unclassified
“…Quando a temperatura é o principal fator limitante, a irrigação, mesmo não sendo capaz de eliminar, pode atenuar a estacionalidade das forrageiras tropicais durante o inverno (BUENO et al, 2019;GOMES et al, 2015;SANCHES et al, 2016).…”
Section: Nos Processos De Intensificação Da Pecuária O Pasto As Culti...unclassified
See 1 more Smart Citation